Physical Restraint: a descriptive study in swiss nursing homes - Hantikainen, Virpi (Nursing ethics, 1998)
This article focuses on the reasons for using physical restraints, their prevalence and nurses’ experiences of their use. The data were collected by means of a questionnaire from nurses, trained nurse’s aids and auxiliary staff (n = 173) in seven Swiss nursing homes. The results showed that physical restraints are used in nursing units, the mean number of restrained residents in each being 3.7 (SD 3.9). However, nursing staff did not necessarily understand and consider the term ‘restraint’ as a restrictive device in its negative sense. The most common reasons indicated for the use of restraint were related to the protection and safety of the residents themselves, the prevention of disturbance of other residents, and the residents’ restlessness and aggressiveness. As for the reasons related to staffing, reference was made to understaffing, a lack of competence on the part of nurses, and the demands of residents, their next of kin and doctors. It was not common practice to inform the elderly residents that they would be restrained, and therefore they were not always aware of what was happening to them and why. Twenty-nine per cent of the respondents reported that the flexibility of their work was affected by the use of physical restraint.